(untitled) (Bangladesh Journal of Animal Science, 2021)
This study was undertaken to evaluate the egg quality parameters of New Hampshire and Giriraja by maintaining four different flocks (lines) of New Hampshire viz. NH-Khajura, NH-Parwanipur, NH-Khumaltar and NH-Pokhara and three different flocks (lines) of Giriraja viz. GR-Pakhribas, GR-Khumaltar and GR-Tarhara. The 40-60 weeks of hatchability, fertility, external and internal egg quality parameters were studied and recorded. A total of 200 birds (40 weeks of age) of each New Hampshire and Giriraja from each line were maintained on deep litter system. Results from this study indicated the significant effect of genotype and respective lines on fertility and hatchability of eggs. Significant (P<0.05) variation in fertility and no significant variation in hatchability for genotypes were found. However, in terms of fertility and hatchability, there were significant variations in different lines. In case of egg weight: no significant (P<0.01) variation was obtained for genotype but lines comparison showed significant variation. Other external egg quality parameters like egg length, egg diameter, shape index, shell thickness were examined for evaluating the genotype and line effect. In all these external egg quality parameters, there were significant (P<0.01) effect of both genotype and lines of birds. For internal egg qualities, yolk weight (g), yolk index, albumen weight and albumen index were checked. Genotype had no significant (P<0.01) effect but lines had significant (P<0.01) effect on yolk weight. In case of yolk index, both genotype and lines of bird had no significant effect. For albumen weight and albumen index, genotype of birds had no significant (P<0.01) effect but lines of bird had significant (P<0.01) effect on both parameters. The study showed that the egg quality parameters of NH (Khajura) were better than that of GR. Among different lines New Hampshire (Khajura) showed better performance in terms of egg quality parameter. Bang. J. Anim. Sci. 2020. 49 (2): 108-118